A facile and light-controllable drug combination for enhanced photopharmacology. Issue 5 (6th January 2023) - Du, Guangxi; Fu, Jielin; Zheng, Yuanqin; Hu, Fuqiang; Shen, Xin; Li, Baolin; Zhao, Xiaohu; Yu, Zhipeng
Abstract : The visible light-regulated drug combination of DBTDA-fused floxacin and azobenzene-linked sulfadiazine against S. aureus. Abstract : We investigated the feasibility of creating cyclic azobenzene/azobenzene-based photo-switchable drugs that can fine-tune antibacterial activity against Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) with light dependence. Furthermore, a "light-controlled drug combination" of these obtained drugs could be reversibly controlled to efficiently improve the antibiotic effect so as to reduce the minimum inhibitory concentrations (MICs) with different wavelength light illumination. Importantly, their antimicrobial activity could be easily manipulated by using light in bacterial patterning studies with high spatiotemporal precision, which might allow for localized activation of drugs and provide an alternative solution for practical clinical application in photopharmacology.